Campus Food Provision as Radical Pedagogy? Following Students on the Path to Equitable Food Systems - Classens, Michael; Adam, Kaitlyn; Crouthers, Sara Deris; Sheward, Natasha; Lee, Rachel (Frontiers in Sustainable Food Systems, 2021)
On campuses across North America, students are actively prefiguring alternatives to the fundamental inequities and unsustainability of the capital-intensive, industrialized food system (Barlett, 2011; Classens and Burton, forthcoming; LaCharite, 2016). While rarely recognized as such, these Campus Food System Alternatives (CFSA) are intensely pedagogical spaces, and often - importantly - are student led and directed. We make the case that CFSA are sites for a “pedagogy of radical hope” (Gannon, 2020, 22) that (a) centre student agency, (b) through informal and prefigurative learning. So far these spaces have received scant scholarly attention, though inasmuch as they constitute pathways toward more equitable and sustainable food systems, while informing liberatory pedagogical practice, we argue that it is high time for CFSA to be taken seriously.